The histone chaperone complex HIR maintains nucleosome occupancy and counterbalances impaired histone deposition in CAF‐1 complex mutants. (March 2015) - Duc, Céline; Benoit, Matthias; Le Goff, Samuel; Simon, Lauriane; Poulet, Axel; Cotterell, Sylviane; Tatout, Christophe; Probst, Aline V.
Summary Chromatin organization is essential for coordinated gene expression, genome stability, and inheritance of epigenetic information. The main components involved in chromatin assembly are specific complexes such as Chromatin Assembly Factor 1 (CAF‐1) and Histone Regulator (HIR), which deposit histones in a DNA synthesis‐dependent or ‐independent manner, respectively. Here, we characterize the role of the plant orthologs Histone Regulator A (HIRA), Ubinuclein (UBN) and Calcineurin Binding protein 1 (CABIN1), which constitute the HIR complex. Arabidopsis loss‐of‐function mutants for the various subunits of the complex are viable, but hira mutants show reduced fertility. We show that loss of HIRA reduces extractable histone H3 protein levels and decreases nucleosome occupancy at both actively transcribed genes and heterochromatic regions. Concomitantly, HIRA contributes to maintenance of silencing of pericentromeric repeats and certain transposons. A genetic analysis based on crosses between mutants deficient in subunits of the CAF‐1 and HIR complexes showed that simultaneous loss of both the CAF‐1 and HIR histone H3 chaperone complexes severely affects plant survival, growth and reproductive development. Our results suggest that HIRA partially rescues impaired histone deposition in fas mutants to preserve nucleosome occupancy, implying plasticity in histone variant interaction and deposition.